The Relationship between Self‐Estimated Intravaginal Ejaculatory Latency Time and International Prostate Symptom Score in Middle‐Aged Men Complaining of Ejaculating Prematurely in China. (29th January 2015) - Zhang, Xiansheng; Tang, Dongdong; Xu, Chuan; Gao, Pan; Hao, Zongyao; Zhou, Jun; Liang, Chaozhao
Abstract Introduction Some factors associated with the four premature ejaculation (PE) syndromes have been studied, but the association between International Prostate Symptom Score (IPSS) and the four PE syndromes has not been investigated. Aims We performed this study to evaluate the association between IPSS and intravaginal ejaculatory latency time (IELT) in men with the four PE syndromes. Methods From June 2012 to January 2014, a total of 690 men aged 40–59 years complaining of ejaculating prematurely and another 452 male healthy subjects of the same age without these complaints were included in this study. Men with the complaints of ejaculating prematurely were classified as one of the four PE syndromes: lifelong PE, acquired PE (APE), variable PE, and subjective PE. Each of them completed a detailed questionnaire including information on demographics, medical and sexual history (e.g., self‐estimated IELT), IPSS, and International Index of Erectile Function‐5. Main Outcome Measures Associations between IPSS and self‐estimated IELT in middle‐aged men with the four PE syndromes. Results Men complaining of ejaculating prematurely reported higher IPSS (11.2 ± 6.0 vs. 5.5 ± 3.3 ) and shorter self‐estimated IELT (2.1 ± 1.6 minutes vs. 4.8 ± 3.3) than men without complaints (P < 0.001 for each). By unilabiate analysis, self‐estimated IELT in men with the four PE syndromes showed significant correlations with IPSS (P < 0.001 for all). After adjusting for age, self‐estimated IELT was negatively associated with IPSS in men with PE complaints (adjusted r = −0.378, P < 0.001). Also, the association was stronger in men with APE (adjusted r = −0.502, P < 0.001). Conclusions Men complaining of ejaculating prematurely reported worse IPSS than men without these complaints. Self‐estimated IELT was negatively associated with IPSS in men complaining of ejaculating prematurely, and the correlation was the strongest in men with APE. Zhang X, Tang D, Xu C, Gao P, Hao Z, Zhou J, and Liang C. The relationship between self‐estimated intravaginal ejaculatory latency time and international prostate symptom score in middle‐aged men complaining of ejaculating prematurely in China. J Sex Med 2015;12:705–712.